KEPUTUSAN PEMBELIAN ITEM VIRTUAL DALAM KONTEKS PERTEMANAN PADA GAMERS MOBILE LEGENDS DI DENPASAR DALAM PERSPEKTIF TPB - I Made Darmayasa; Ni Ketut Arniti (Journal of Innovation Research and Knowledge, 2026)
Abstract: This study aims to analyze the role of social influence within friendship environments in shaping the decision to purchase virtual items among Mobile Legends players in Denpasar City. The research applies a descriptive qualitative method using the Theory of Planned Behavior (TPB) as its analytical framework. The findings reveal that social influence plays a significant role in shaping players’ perceptions, intentions, and purchasing behavior of virtual items. Based on TPB, there are three main factors influencing behavior: attitude toward behavior, subjective norms, and perceived behavioral control. These factors are reflected in players’ experiences, interactions with friends, and their ability to control purchasing decisions. Social influence emerges through both informational and normative processes, where players are indirectly shaped by their peers through shared experiences, in-game interactions, and exposure to virtual items used by others. By internalizing these dynamics, players develop interest and intention to purchase virtual items, although the final decision remains dependent on individual control and financial considerations. Therefore, the role of social influence within friendship networks, combined with individual control, serves as a key element in shaping virtual item purchasing behavior among Mobile Legends players in Denpasar City